EVALUATION OF MEAN PLATELET VOLUME LEVEL AS A BIOMARKER IN ACUTE APPENDICITIS IN CHILDREN AND ADOLESCENT: A RETROSPECTIVE STUDY - ASHISH JAWARKAR,; HIREN VAGHELA,; KETAN MANGUKIYA, (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study aims to investigate the diagnostic value of mean platelet volume (MPV) in early diagnosis of acute appendicitis cases in children and adolescents. Methods: 50 patients with the age of ≤20 years were chosen retrospectively from the case files of the patients admitted to the hospital between May 2021 and May 2022 in whom the definite diagnosis of acute appendicitis was confirmed with postoperative pathological examination. This group was labeled as case group. The control group consists of 50 patients with the age of ≤20 years who came for the regular health checkups at our institute. All blood samples were analyzed for complete blood count that includes MPV also in a fully automated 6-part hematology cell counter. These data of both the groups were analyzed statically to calculate p value using the online Student’s t-test calculator. The value p<0.05 is considered to be statistically significant. Results: Majority of acute Appendicitis cases (n=30, 60%) belong to 16–20 years, followed by 24% in 11–15-year-age group. The mean age was 14.96±2.75 years. According to gender, 66% (n=33) were male. The mean platelet count in the case of group was 3.10±0.5 Lakhs/ml whereas in the case of Group was 2.86±0.7 lakhs/mL. There was no statistically significant difference among the group with respect to platelet count (p=0.188 >0.05) The MPV in the case of case Group was 7.92±0.3 fL whereas in the case of the control group was 8.62±0.4 fL. There was a statistically significant difference among the in terms of MPV (p=0.04 <0.05). Conclusion: The diagnosis of acute appendicitis in children and adolescents is aided by a decrease in MPV. The rate of negative appendectomy in children and adolescents with suspected acute appendicitis may decrease if the clinician pays attention to the MPV (which is determined routinely as a part of automated count) alongside other parameters and clinical evaluations.